If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -24 + -2m = -2m + -4(5m + 1) Reorder the terms: -24 + -2m = -2m + -4(1 + 5m) -24 + -2m = -2m + (1 * -4 + 5m * -4) -24 + -2m = -2m + (-4 + -20m) Reorder the terms: -24 + -2m = -4 + -2m + -20m Combine like terms: -2m + -20m = -22m -24 + -2m = -4 + -22m Solving -24 + -2m = -4 + -22m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '22m' to each side of the equation. -24 + -2m + 22m = -4 + -22m + 22m Combine like terms: -2m + 22m = 20m -24 + 20m = -4 + -22m + 22m Combine like terms: -22m + 22m = 0 -24 + 20m = -4 + 0 -24 + 20m = -4 Add '24' to each side of the equation. -24 + 24 + 20m = -4 + 24 Combine like terms: -24 + 24 = 0 0 + 20m = -4 + 24 20m = -4 + 24 Combine like terms: -4 + 24 = 20 20m = 20 Divide each side by '20'. m = 1 Simplifying m = 1
| 11i-(4+7i)= | | 6(x+5)+3=2(x+4)+4(x+7)-3 | | (-3x-4)-(3x+3)= | | (X+3)6=(2x-1)3 | | (x-3)=4x-9 | | -5+9=-4x-3 | | y=15+10x-5x^2 | | 7(2+x)+15=10x-4 | | (5x+5)-(2x-4)= | | y=-1.5+50 | | -7+3(1+5v)=-24 | | 3(x+5)=2(3x-12) | | 35+.15x=20+.35x | | -4x-(x-4)=3(-2x-1) | | y=1x+-6 | | -7y-5+3=19 | | 6e-60=-4(e+5) | | 6x-4(1.5x)=1 | | u=y+x-k | | 5n-4-8n=-33 | | -6(2x-9)=2(x-8)-11 | | ln*(x+4)-ln*(x-6)=ln*17 | | -28=-6+9(s+3) | | 9=-(1-5x) | | 3.9(z+5.7)=8.19+7.8z | | 15x-18=8x | | -(7b-6)=2b+33 | | y-4=1-x | | y-4=1-x# | | 4-7.2x+2=0.8x+4.5 | | 5c+2=3c-2 | | 2+4(1-4n)=38 |